Analysis of the Use of Ergonomic Trolley on Musculoskeletal Complaints on Worker Transporting Gallons of Water and LPG 12 Kg - I Gede Santosa; I Nyoman Budiartana (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Everyday, the use of water and gas is very important for human life, especially drinking water and LPG gas. As time goes by, the need for drinking water and LPG gas is increasing every day, because people are aware of their health and desire to live a more practical life. With the increasing demand for drinking water and LPG gas, many drinking water and LPG gas companies are packaged with large capacities. such as gallon water with a capacity of 19 liters and LPG gas measuring 12 kg. If the weight of gallon water reaches 19kg and 12kg LPG gas reaches 27kg, this can cause workers to be tired and overwhelmed to serve consumers. Moreover, consumers live on the 2nd floor apartment which must still be served. Lifting workers in general, lift gallons of water and 12kg LPG gas using their hands and carry them and the work is done repeatedly, this can cause muscle injuries, especially in the wrists, elbows and shoulders. In addition, the time used is relatively long due to the limitations of workers who can only carry 1 gallon or 1 piece of 12 kg LPG gas, especially customers with long haul-haul distances, which require workers to carry them without any tools. As a solution to these problems, an ergonomically designed trolley was made so that the lifting and transport workers could work in a healthy, safe and comfortable manner. In this study, a 12kg LPG gas carrier and 2 gallons of water will be designed and continued by analyzing the use of these tools for workers in terms of musculoskeletal muscle complaints and fatigue levels. Specifications This trolley has been ergonomically designed that has been adapted to the anthropometry of the worker's body and is capable of transporting 2 gallons of aqua or 2 12 kg LPG gas. The trolley design results with dimensions: 70 cm wide and 140 cm high with a weight of 60 kg, quite simple to move around The results of testing and analysis of musculoskeletal complaints and fatigue levels were obtained that: The average musculoskeletal complaints of workers before working using a trolley was 44.02 (±2.56) and the average musculoskeletal complaint after working using a trolley was 33.04 (±4.17) which means there is a decrease in musculoskeletal complaints by 24.9% %. The average level of fatigue of workers before working using a trolley is 44.11 (±2.17) and the average level of fatigue after working using a trolley is 33.03 (±3.22) which means there is a decrease in the level of fatigue by 25.1%.